Image of Bali from Western Perspective in Jamie James' A Tale of Bali and Elizabeth Gibert's Eat, Pray, Love - Seswita, Seswita; Yeni, Marliza (English Department, Faculty of Humanities, Andalas University, 2023)
Many foreign writers have expressed their fascination with Bali in their works, among them are Jamie James in Andrew and Joey: a tale of Bali and Elizabeth Gilbert in Eat, Pray, Love. The two authors wrote about Bali from their personal experience dring their stay in that island. Some images created in the works are seen and analyzed through the prespective of Postcolonialism and New Criticism. This article presents how the two authors depicts Bali as an extravagant place in Eastern country which has adopted some Western values. The negative image is delivered to oppose the idea of Bali as the perfect island; moreover, as part of Indonesia, Bali still has some weaknesses to strengthen and truly support that it is part of Indonesia. The writer admits that this article is far from perfect. Due to the limitation of thinking and time, some more aspects can be explored more profoundly in terms of the image of Bali in these two works. Hence, there are still a lot of literary works that also talk about and discuss the image of Bali. Hopefully, there will be anyone who, willingly or even the writer himself, could continue the research and find out more about the images of Bali from the Western perspective as seen in some other novels and works.